The craft of peroxisome purification: a technical survey through the decades - Islinger, Markus; Manner, Andreas; Völkl, Alfred (Proteomics of peroxisomes, 2018)
Purification technologies are one of the working horses in organelle proteomics studies as they guarantee the separation of organelle-specific proteins from the background contamination by other subcellular compartments. The development of methods for the separation of organelles was a major prerequisite for the initial detection and characterization of peroxisome as a discrete entity of the cell. Since then, isolated peroxisomes fractions have been used in numerous studies in order to characterize organelle-specific enzyme functions, to allocate the peroxisome-specific proteome or to unravel the organellar membrane composition. This review will give an overview of the fractionation methods used for the isolation of peroxisomes from animals, plants and fungi. In addition to “classic” centrifugation-based isolation methods, relying on the different densities of individual organelles, the review will also summarize work on alternative technologies like free-flow-electrophoresis or flow field fractionation which are based on distinct physicochemical parameters. A final chapter will further describe how different separation methods and quantitative mass spectrometry have been used in proteomics studies to assign the proteome of PO.